Chemical composition, therapeutic potential and perspectives of Foeniculum vulgare - Garg, Chanchal; Khan, S A; Ansari, S. H.; Suman, Arti; Garg, Munish (Pharmacognosy Reviews)
Foeniculum vulgare is a widely distributed plant in most tropical and subtropical countries and have long been used in folk medicines to treat obstruction of the liver, spleen and gall bladder and for digestive complaints such as colic, indigestion, nausea and flatulence. In recent years the interest in this plant has increased considerably with substantial progress on its chemical and pharmacological properties. This review discusses the current knowledge of its chemistry, the various compounds isolated and pharamcological studies conducted. These studies carried out with the extracts and volatile oil support most of the reports of using this plant in folk medicines. However, well controlled, double-binding clinical trials are lacking. Several compounds including trans-anethole, estragole, fenchone and polyphenolics were isolated from this plant and some of these interact with potential mechanisms of the body. Together this data strongly supports the view that this plant has potential beneficial therapeutic actions in the management of bacterial and fungal infections, colic pain and lipid peroxidation.
Keywords: Foeniculum vulgare; volatile oil; antibacterial; antifungal; mosquito repellent; antioxidant